Business Communication Strategies to Improve Customer Relationships in the Digital Age - Jordi Hairul Rafli; Havis Aravik; Choiriyah, Choiriyah; Emilia Sari (Penerbit dan Percetakan CV. Picmotiv, 2025)
This study aims to analyze effective business communication strategies in building and enhancing customer relationships in the digital era. The benefit of this research is to provide practical insights for business practitioners in developing communication approaches that are adaptive to technological developments, as well as to offer a scientific foundation for academics in the field of digital business communication studies. This research employs a qualitative method with a literature review approach and descriptive analysis of various academic journals and relevant case studies. The findings reveal four key strategies that significantly impact customer relationship enhancement: the use of social media as a two-way communication channel, the application of data-driven personalization, the improvement of fast and responsive customer service, and the utilization of Customer Relationship Management (CRM) technology for structured and sustainable communication. These strategies have proven effective in increasing customer satisfaction, loyalty, and emotional engagement with brands. Therefore, companies that can integrate digital communication with data and technology-based approaches are more likely to achieve a stronger competitive advantage in the digital marketplace.